Evaluation of low cost radiant cooling panel in a test room with passively cooled water - Muhammad Syukri Imran, Abdullah; Azhaili, Baharun; Siti Halipah, Ibrahim; Wan Azlan, Wan Zainal Abidin (TAF Publishing, 2017)
Public acceptance in low energy hydronic radiant cooling system is almost none in country like Malaysia. This is due to the low awareness of the performance and benefit of such system in the country as well as higher initial construction cost. With the aim of long term energy and cost saving this study looks into the performance of custom built radiant cooling surface panel that was retrofitted in a test room located in Kuching Sarawak. In climate condition like Malaysia where only cooling is required, the radiant panel needs only to be a cooling surface unlike its overseas counterpart that heats or cools interchangeably according to the changing seasons. This allows the use of alternative low cost material such as PVC to replace the more common radiant tubing like copper or cross-linked Polyethylene (PEX) tube. A test room was retrofitted with PVC tubing radiant ceiling panel and connected to a chill water tank. The water was passively cooled during the night using the pitch roof as a heat exchanger to chill the water to as low as 24⁰C.The water was then used to charge the hydronic ceiling radiant panel during the day time when the outdoor temperature exceeds 30⁰C. The experiment shows that the system was able to maintain an indoor temperature to about 30⁰C when the outdoor temperature peaked to 34⁰C while providing acceptable thermal comfort. The experiment showed that the use of the hydronic radiant panel with free night cooled water as its coolant have significant energy saving potential while at the same time provide an acceptable room thermal comfort. The locally built radiant panel and easy to install night cooling rig could be an attractive choice as a Malaysian building cooling system that complies to a bioclimatic building principle